CFD simulations of shell-side flow in a shell-and-tube type heat exchanger with and without baffles. (2nd April 2016) - Pal, Eshita; Kumar, Inder; Joshi, Jyeshtharaj B.; Maheshwari, N.K.
Abstract: Shell-and-tube heat exchanger has been extensively used in industrial and research fronts for more than a century. However, most of its design procedures are based on empirical correlations extracted from experimental data of long length shell and tube heat exchanger. In this paper, an attempt has been made to investigate the complex flow and temperature pattern in such a short shell and tube type heat exchanger, with and without baffles in the shell side. Heat exchangers of length by hydraulic diameter ratio between 7 < L / D h < 21 ( 0.15 m < D S < 0.6 m ) for unbaffled and L / D h < 7 ( D S = 0.09 m ) for baffled heat exchangers are analysed using CFD code OpenFOAM-2.2.0 for different mass flow rates. It was observed that the cross flow near the nozzle region has a significant contribution towards the heat transfer, hence the conventional heat transfer correlations do not apply to these short heat exchangers. Furthermore, a sensitivity study of turbulence models was performed and it was observed that the standard k – ε model gives best results for the velocity profile as well as heat transfer, provided average y + of the first node adjacent to the heat transfer surface is maintained greater than 15. The commonly used boundary conditions at the exit are not realistic, as it tends to give either incorrect flow and temperature fields, or the solution was found to diverge. Through a sensitivity study of the exit length, it was found that exit length to shell side velocity ratio of 2.5 is required for proper convergence. Finally the effect of flow field on shell side heat transfer coefficient and a comparison with analytical methods are presented. Abstract : Highlights: y + > 15 using std k – ε model is recommended for CFD simulation of heat exchanger. For L / D h < 21, Nusselt number is largely controlled by cross flow in nozzle area. CFD studies reveal recirculation zones and leakage flows in shell side flow. Outlet length to shell velocity ratio must be at least 2.5 for code convergence.